DETERMINAN AKUNTABILITAS PENGELOLAAN KEUANGAN MASJID DI KOTA MATARAM - Pratama, Fadhli Dzal Khaliq; Animah, Animah; Nurabiah, Nurabiah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This research was conducted to examine the determinants of financial management accountability carried out by mosque management in the financial management section consisting of the chairman of the mosque management and the mosque treasurer at mosques in Mataram City which are listed on the simas.kemenag.go.id website database totaling 274 mosques. The research sample totaled 68 mosques, which were selected based on two criteria contained in the simas.kemenag.go.id website, namely: 1) Mosques that have a congregation of 200 people or more, 2) Mosques that have a number of mosque administrators of 20 people or more. Data analysis was performed using the Smart PLS application. The research findings reveal that the competence of human resources and the utilization of information technology have no effect on financial management accountability. Meanwhile, the internal control system has an influence on financial management accountability.